Equity valuation of Tesco Plc. - Schmitz, Clemens (2016)
This dissertation aimed to value the British retailer Tesco Plc. The objective was to determine a target price for the company and as a consequence determine a buy or sell recommendation when comparing it to the current market price. After the state of the art of literature regarding equity valuation has been assessed, the retail industry as well as Tesco have been analysed in more detail. Based on this, the retail business of Tesco has been valued using the Adjusted Present Value method. Furthermore a multiples valuation was performed, which did not confirm the results obtained under the intrinsic valuation. The banking business of Tesco has been valued using both, the DuPont methodology as well as a multiples approach, while the Chinese Joint Venture has been valued based on a recent transaction. The sum of the parts results in a value of 2.85 GBP per share. As the share of Tesco trades at 1.83 GBP as per October 31st 2015, a buy recommendation is concluded. A comparison with the valuation of Bernstein investment bank is conducted and differences in valuation are evaluated.